Analysis Of Wireless Energy Transfer Systems By Methods Inductive Resonance - Siti Suriyatni; Beni Satria; Amani Darma Tarigan (Jurnal Scientia, 2024)
This research investigates wireless energy transfer techniques using the inductive resonance method. This method utilizes resonance between the sending and receiving coils to increase energy transfer efficiency. The main focus is the analysis of resonance characteristics that affect energy transfer efficiency, such as resonance frequency, coil quality, and distance between transmitter and receiver. This research uses an analytical approach to measure key parameters such as voltage and current on both sides of the transfer. The collected data is analyzed to understand the relationship between resonance parameters and overall system efficiency. The analysis results will be used to validate the mathematical model developed to optimize the system design. This research is expected to provide valuable insights to increase efficiency and transfer distance in the application of inductive resonance-based wireless energy transfer technology.